PVDF (Polyvinylidene Fluoride) profile and preparation process thereof
By surface modification of the nano-silica filler and copolymerizing with PVDF, the problems of large shrinkage and unstable dimensional accuracy during the molding of PVDF materials are solved, and PVDF profiles with low forming shrinkage and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202411686398.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The shrinkage rate of PVDF materials during the molding process is large, resulting in unstable dimensional accuracy and ordinary fillers are difficult to be compatible with PVDF well dispersed.
Nanosilica filler is used for surface modification, adamantane structure and trifluoroethyl groups are introduced, and the dispersion compatibility of the filler and PVDF is improved through specific silane monomer reaction and copolymerization processes, thereby reducing the forming shrinkage rate.
It effectively reduces the forming shrinkage rate of PVDF profiles, improves dimensional accuracy, and enhances the mechanical properties of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic preparation, and in particular to a PVDF profile and a preparation process thereof. Background Art
[0002] PVDF stands for polyvinylidene fluoride. It is a polymer material that can be formed by high-temperature extrusion. Its crystallinity is between 65% and 78%, and its density is 1.77-1.8g / cm 3 The melting point is as high as 172℃, the heat deformation temperature is between 112-145℃, and the continuous working temperature range is -40℃ to 150℃. Its unique chemical structure and excellent physical properties give PVDF materials a series of key advantages. The special molecular structure of alternating CH2 and CF2 in its polymer chain makes PVDF have both the excellent processing properties of polyethylene and the excellent chemical resistance close to polytetrafluoroethylene. PVDF does not contain UV stabilizers, thermal stabilizers, softeners, lubricants or flame retardant additives, so it has extremely high purity and stability; PVDF has inherent excellent flame retardant properties, and its oxygen index is 46%. It can easily reach the UL94 V0 flame retardant grade without adding any flame retardants; PVDF has good chemical resistance, it hardly reacts with any medium, and is extremely chemically inert to most acids, alkalis, salts and a variety of organic solvents, and its surface is smooth and not easy to adhere to materials. It is one of the best materials for pumps, valves, pipes, pipe fittings, storage tanks and heat exchangers in the fluid handling system of petrochemical equipment as a whole or lining; compared with other plastic materials, PVDF material has higher tensile strength, impact resistance and wear resistance, and can maintain good rigidity and toughness even in low temperature environments; PVDF is also an excellent insulating material with a low dielectric constant and loss factor, suitable for insulation protection in electronics, electricity and other fields.
[0003] Based on the above advantages of PVDF, it is widely used in the fields of plates, rods, pipes, welding materials, etc., but PVDF has a large molding shrinkage rate, and it is difficult to maintain stable dimensional accuracy when it is formed as plates, rods, pipes or welding materials. Its shrinkage rate can be reduced by adding fillers, but the chemical inertness of PVDF determines that ordinary fillers are difficult to disperse and be compatible with it well. Summary of the invention
[0004] In view of the above problems, the present invention provides a PVDF profile and a preparation process thereof.
[0005] The purpose of the present invention is achieved by the following technical solutions: A PVDF profile includes polyvinylidene fluoride and a filler, wherein the preparation method of the filler includes the following steps: (1) Weigh 4-bromobenzocyclobutene and dissolve it in tetrahydrofuran solvent, add magnesium powder, slowly add dimethylchlorosilane under stirring, continue stirring and react for 10-20 hours after the addition is completed, centrifuge and separate the precipitate after the reaction is completed, and evaporate the solvent under reduced pressure to obtain product A; (2) Under a protective atmosphere, triethoxyvinylsilane is dissolved in tetrahydrofuran solvent, iodine and magnesium powder are added, and 2-adamantane-4-bromo-1-(2,2,2-trifluoroethoxy)benzene is slowly added under stirring conditions. After the addition is completed, the stirring reaction is continued for 5-10 hours. After the reaction is completed, cyclohexane is added to dilute the reaction system, and the precipitate is separated by centrifugation. The solvent is evaporated under reduced pressure to obtain product B; the product A is dissolved in toluene solvent, the product B and perfluorotriphenylboron are added under stirring conditions, and the stirring reaction is continued at room temperature for 2-5 hours. After the reaction is completed, the product is concentrated under reduced pressure, and the product is purified by a chromatographic column to remove unreacted reactants. The solvent is evaporated under reduced pressure to obtain product C; (3) Surface-treating nano-silica with a vinyl silane coupling agent to obtain a precursor product; dissolving the C product in mesitylene solvent, adding the precursor product and stirring and dispersing, stirring and refluxing at 150-160° C. for 2-8 hours, separating and precipitating after cooling, evaporating the solvent in the precipitate, heating to 210-250° C. under a protective atmosphere and keeping the temperature for 1-3 hours, and cooling to obtain the product.
[0006] In some preferred embodiments, the PVDF profile may also be blended with other polymers, such as polytetrafluoroethylene, polyoxymethylene, polyimide, polyetherimide, polyphenylene ester or a mixture thereof.
[0007] In some preferred embodiments, the weight average molecular weight of the polyvinylidene fluoride is between 100,000 and 1,000,000.
[0008] In some preferred embodiments, the mass ratio of polyvinylidene fluoride to the filler is (6-10):1.
[0009] In some preferred embodiments, the mass ratio of the 4-bromobenzocyclobutene to the magnesium powder and the dimethylchlorosilane in step (1) is 10:(1.8-2):(10-11).
[0010] In some preferred embodiments, the mass ratio of the triethoxyethylenesilane to the iodine, the magnesium powder, and the 2-adamantane-4-bromo-1-(2,2,2-trifluoroethoxy)benzene in step (2) is 10:(0.13-0.15):(1.34-1.52):(14-16).
[0011] In some preferred embodiments, the mass ratio of the product A to the product B and the perfluorotriphenylboron in step (2) is 10:(13-15):(0.07-0.09).
[0012] In some preferred embodiments, the particle size of the nano-silicon dioxide in step (3) is 100-1000 nm.
[0013] In some preferred embodiments, the vinyl silane coupling agent in step (3) is vinyl trimethoxy silane, vinyl methoxy diethoxy silane, vinyl triethoxy silane, vinyl ethoxy diisopropoxy silane, vinyl triisopropoxy silane, γ-methacryloxy propyl trimethoxy silane, γ-methacryloxy propyl triisopropoxy silane.
[0014] In some preferred embodiments, the mass ratio of the C product to the precursor product in step (3) is (1-2.4):1.
[0015] In some preferred embodiments, the PVDF profile is applied in the form of a plate, a rod, a tube or a welding material, and its forming method includes extrusion and molding.
[0016] Another object of the present invention is to provide a preparation process of the PVDF profile, which specifically comprises the following steps: S1, prepare the filler for standby use; S2, mixing the polyvinylidene fluoride and the filler, and then extruding and granulating at 250-300° C. to obtain the obtained product.
[0017] The beneficial effects of the present invention are: In view of the problem that PVDF has a large shrinkage rate and unstable dimensional accuracy when it is used as a profile in the prior art, the present invention provides a PVDF profile with low forming shrinkage rate. The surface of the PVDF profile is modified on the basis of a nano-silica filler to introduce an adamantane structure and a trifluoroethyl group, thereby improving its dispersion compatibility with PVDF and effectively reducing its forming shrinkage rate. Specifically, the present invention uses 4-bromobenzocyclobutene and dimethylchlorosilane as raw materials to react, grafts benzocyclobutene on the silane monomer, and reacts triethoxyethylene silane with 2-adamantane-4-bromo-1- (2,2,2-Trifluoroethoxy)benzene is used as a raw material to graft adamantane and trifluoroethyl onto vinyl silane monomer, and then the grafted silane monomer is reacted with the grafted vinyl silane monomer to obtain a modified silane monomer having vinyl, cyclobutenyl, adamantane and trifluoroethyl. Finally, it is copolymerized with nano-silica modified with vinyl surface, and a layer of organic silane modified polymer is chemically bonded to the surface of the nano-silica, which improves the affinity and compatibility between the filler and the resin and reduces the molding shrinkage of the resin. The introduction of the adamantane structural group can also improve the mechanical properties of the resin. DETAILED DESCRIPTION
[0018] The present invention is further described in conjunction with the following examples. Example 1
[0019] A PVDF profile is composed of polyvinylidene fluoride and filler, and its preparation process comprises the following steps: S1, preparing the filler (1) Weigh 4-bromobenzocyclobutene and dissolve it in tetrahydrofuran solvent, add magnesium powder, slowly add dimethylchlorosilane under stirring conditions, continue stirring and react for 14 hours after the addition is completed, centrifuge and separate the precipitate after the reaction is completed, and evaporate the solvent under reduced pressure to obtain product A; wherein the mass ratio of the 4-bromobenzocyclobutene to the magnesium powder and the dimethylchlorosilane is 10:1.9:10.7; (2) Under a nitrogen atmosphere, triethoxyvinylsilane was dissolved in tetrahydrofuran solvent, iodine and magnesium powder were added, and 2-adamantane-4-bromo-1-(2,2,2-trifluoroethoxy)benzene (CAS No. 929000-50-0) was slowly added under stirring conditions. After the addition was completed, the reaction was continued to be stirred for 8 hours. After the reaction was completed, cyclohexane of an equal volume to the reaction system was added to dilute it, and the precipitate was separated by centrifugation. The solvent was evaporated under reduced pressure to obtain product B; the product A was dissolved in toluene solvent, and the product B and perfluorotriphenylboron were added under stirring conditions. The mixture was stirred and reacted for 3 hours at room temperature. After the reaction was completed, the mixture was concentrated under reduced pressure and placed into a chromatographic column (500 mesh silica gel). The mixture was purified using n-hexane as a mobile phase to remove unreacted reactants. The solvent was evaporated under reduced pressure to obtain product C. The mass ratio of the triethoxyethylenesilane to the iodine element, the magnesium powder, and the 2-adamantane-4-bromo-1-(2,2,2-trifluoroethoxy)benzene was 10:0.14:1.45:14.9. The mass ratio of the product A to the product B and the perfluorotriphenylboron was 10:14.2:0.08. (3) Dispersing nano-silica in an ethanol aqueous solution of vinyltrimethoxysilane at a concentration of 0.1 mol / L (v / v=9 / 1), stirring the reaction for 4 hours, separating the precipitate, washing it with ethanol and deionized water, and drying it to obtain a precursor product; dissolving the C product in a mesitylene solvent, adding the precursor product and stirring and dispersing it, stirring and refluxing at 160°C for 5 hours, separating the precipitate after cooling, and evaporating the solvent in the precipitate, heating it to 240°C under a protective atmosphere and keeping it warm for 1.5 hours, and cooling it to obtain the filler; wherein the average particle size of the nano-silica is 400 nm; the mass ratio of the C product to the precursor product is 1.7:1; S2. The polyvinylidene fluoride is mixed with the filler, and then extruded and granulated at 270° C., wherein the weight average molecular weight of the polyvinylidene fluoride is 450,000; and the mass ratio of the polyvinylidene fluoride to the filler is 7:1. Example 2
[0020] A PVDF profile is composed of polyvinylidene fluoride and filler, and its preparation process comprises the following steps: S1, preparing the filler (1) Weigh 4-bromobenzocyclobutene and dissolve it in tetrahydrofuran solvent, add magnesium powder, slowly add dimethylchlorosilane under stirring conditions, continue stirring and react for 14 hours after the addition is completed, centrifuge and separate the precipitate after the reaction is completed, and evaporate the solvent under reduced pressure to obtain product A; wherein the mass ratio of the 4-bromobenzocyclobutene to the magnesium powder and the dimethylchlorosilane is 10:1.9:10.7; (2) Under a nitrogen atmosphere, triethoxyvinylsilane was dissolved in tetrahydrofuran solvent, iodine and magnesium powder were added, and 2-(1-adamantyl)-4-bromoanisole (CAS No. 104224-63-7) was slowly added under stirring conditions. After the addition was completed, the reaction was continued to be stirred for 8 hours. After the reaction was completed, cyclohexane of an equal volume to the reaction system was added to dilute the reaction system, and the precipitate was separated by centrifugation. The solvent was evaporated under reduced pressure to obtain product B; the product A was dissolved in toluene solvent, and the product B and perfluorotriphenylboron were added under stirring conditions. The mixture was stirred and reacted for 3 hours at room temperature. After the reaction was completed, the mixture was concentrated under reduced pressure and placed into a chromatographic column (500 mesh silica gel). The mixture was purified using n-hexane as a mobile phase to remove unreacted reactants. The solvent was evaporated under reduced pressure to obtain product C. The mass ratio of the triethoxyvinylsilane to the iodine element, the magnesium powder, and the 2-(1-adamantyl)-4-bromoanisole was 10:0.14:1.45:14.9. The mass ratio of the product A to the product B and the perfluorotriphenylboron was 10:14.2:0.08. (3) Dispersing nano-silica in an ethanol aqueous solution of vinyltrimethoxysilane at a concentration of 0.1 mol / L (v / v=9 / 1), stirring the reaction for 4 hours, separating the precipitate, washing it with ethanol and deionized water, and drying it to obtain a precursor product; dissolving the C product in a mesitylene solvent, adding the precursor product and stirring and dispersing it, stirring and refluxing at 160°C for 5 hours, separating the precipitate after cooling, and evaporating the solvent in the precipitate, heating it to 240°C under a protective atmosphere and keeping it warm for 1.5 hours, and cooling it to obtain the filler; wherein the average particle size of the nano-silica is 400 nm; the mass ratio of the C product to the precursor product is 1.7:1; S2. The polyvinylidene fluoride is mixed with the filler, and then extruded and granulated at 270° C., wherein the weight average molecular weight of the polyvinylidene fluoride is 450,000; and the mass ratio of the polyvinylidene fluoride to the filler is 7:1. Example 3
[0021] A PVDF profile is composed of polyvinylidene fluoride and filler, and its preparation process comprises the following steps: S1, preparing the filler (1) Weigh 4-bromobenzocyclobutene and dissolve it in tetrahydrofuran solvent, add magnesium powder, slowly add dimethylchlorosilane under stirring conditions, continue stirring and react for 14 hours after the addition is completed, centrifuge and separate the precipitate after the reaction is completed, and evaporate the solvent under reduced pressure to obtain product A; wherein the mass ratio of the 4-bromobenzocyclobutene to the magnesium powder and the dimethylchlorosilane is 10:1.9:10.7; (2) Under a nitrogen atmosphere, triethoxyethylenesilane was dissolved in tetrahydrofuran solvent, iodine and magnesium powder were added, 1-bromo-4-(2,2,2-trifluoro-ethoxy)benzene (CAS No. 106854-77-7) was slowly added under stirring conditions, and the stirring reaction was continued for 8 hours. After the reaction was completed, cyclohexane of the same volume as the reaction system was added to dilute, and the precipitate was separated by centrifugation. The solvent was evaporated under reduced pressure to obtain product B; the product A was dissolved in toluene solvent, and the product B and perfluorotriphenylboron were added under stirring conditions. The mixture was stirred and reacted for 3 hours at room temperature. After the reaction was completed, the mixture was concentrated under reduced pressure and placed into a chromatographic column (500 mesh silica gel). The mixture was purified using n-hexane as a mobile phase to remove unreacted reactants. The solvent was evaporated under reduced pressure to obtain product C. The mass ratio of the triethoxyethylenesilane to the iodine element, the magnesium powder, and the 1-bromo-4-(2,2,2-trifluoro-ethoxy)benzene was 10:0.14:1.45:14.9. The mass ratio of the product A to the product B and the perfluorotriphenylboron was 10:14.2:0.08. (3) Dispersing nano-silica in an ethanol aqueous solution of vinyltrimethoxysilane at a concentration of 0.1 mol / L (v / v=9 / 1), stirring the reaction for 4 hours, separating the precipitate, washing it with ethanol and deionized water, and drying it to obtain a precursor product; dissolving the C product in a mesitylene solvent, adding the precursor product and stirring and dispersing it, stirring and refluxing at 160°C for 5 hours, separating the precipitate after cooling, and evaporating the solvent in the precipitate, heating it to 240°C under a protective atmosphere and keeping it warm for 1.5 hours, and cooling it to obtain the filler; wherein the average particle size of the nano-silica is 400 nm; the mass ratio of the C product to the precursor product is 1.7:1; S2. The polyvinylidene fluoride is mixed with the filler, and then extruded and granulated at 270° C., wherein the weight average molecular weight of the polyvinylidene fluoride is 450,000; and the mass ratio of the polyvinylidene fluoride to the filler is 7:1. Example 4
[0022] A PVDF profile is composed of polyvinylidene fluoride and filler. The preparation process is as follows: polyvinylidene fluoride is mixed with nano-silica filler, and then extruded and granulated at 270°C to obtain the profile. The weight average molecular weight of the polyvinylidene fluoride is 450,000 on average. The mass ratio of the polyvinylidene fluoride to the nano-silica filler is 7:1.
[0023] Taking polyvinylidene fluoride (PVDF) without filler as control, the shrinkage rate and mechanical properties of the PVDF profiles described in Examples 1-4 were tested, wherein the shrinkage rate test was carried out with reference to the international standard ISO294-4; the bending performance test was carried out with reference to the national standard GB / T9341-2008; and the tensile performance test was carried out with reference to the national standard GB / T1040.2-2006. The test results are as follows:
[0024] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PVDF profile, characterized in that: The invention comprises polyvinylidene fluoride and a filler, and the preparation method of the filler comprises the following steps: (1) Weigh 4-bromobenzocyclobutene and dissolve it in tetrahydrofuran solvent, add magnesium powder, slowly add dimethylchlorosilane under stirring, continue stirring and react for 10-20 hours after the addition is completed, centrifuge and separate the precipitate after the reaction is completed, and evaporate the solvent under reduced pressure to obtain product A; (2) Under a protective atmosphere, triethoxyvinylsilane is dissolved in tetrahydrofuran solvent, iodine and magnesium powder are added, and 2-adamantane-4-bromo-1-(2,2,2-trifluoroethoxy)benzene is slowly added under stirring conditions. After the addition is completed, the stirring reaction is continued for 5-10 hours. After the reaction is completed, cyclohexane is added to dilute the reaction system, and the precipitate is separated by centrifugation. The solvent is evaporated under reduced pressure to obtain product B; the product A is dissolved in toluene solvent, the product B and perfluorotriphenylboron are added under stirring conditions, and the stirring reaction is continued at room temperature for 2-5 hours. After the reaction is completed, the product is concentrated under reduced pressure, and the product is purified by a chromatographic column to remove unreacted reactants. The solvent is evaporated under reduced pressure to obtain product C; (3) Surface-treating nano-silica with a vinyl silane coupling agent to obtain a precursor product; dissolving the C product in mesitylene solvent, adding the precursor product and stirring and dispersing, stirring and refluxing at 150-160° C. for 2-8 hours, separating and precipitating after cooling, evaporating the solvent in the precipitate, heating to 210-250° C. under a protective atmosphere and keeping the temperature for 1-3 hours, and cooling to obtain the product.
2. A PVDF profile according to claim 1, characterized in that: The weight average molecular weight of the polyvinylidene fluoride is 100,000-1,000,000.
3. A PVDF profile according to claim 1, characterized in that: The mass ratio of polyvinylidene fluoride to the filler is (6-10):
1.
4. A PVDF profile according to claim 1, characterized in that: The mass ratio of the 4-bromobenzocyclobutene to the magnesium powder and the dimethylchlorosilane in step (1) is 10:(1.8-2):(10-11).
5. A PVDF profile according to claim 1, characterized in that: In step (2), the mass ratio of the triethoxyethylenesilane to the iodine element, the magnesium powder, and the 2-adamantane-4-bromo-1-(2,2,2-trifluoroethoxy)benzene is 10:(0.13-0.15):(1.34-1.52):(14-16).
6. A PVDF profile according to claim 1, characterized in that: In step (2), the mass ratio of the product A to the product B and the perfluorotriphenylboron is 10:(13-15):(0.07-0.09).
7. A PVDF profile according to claim 1, characterized in that: The particle size of the nano-silicon dioxide in step (3) is 100-1000 nm.
8. The PVDF profile according to claim 1, characterized in that: The vinyl silane coupling agent in step (3) is vinyl trimethoxy silane, vinyl methoxy diethoxy silane, vinyl triethoxy silane, vinyl ethoxy diisopropoxy silane, vinyl triisopropoxy silane, γ-methacryloxy propyl trimethoxy silane, γ-methacryloxy propyl triisopropoxy silane.
9. A PVDF profile according to claim 1, characterized in that: The mass ratio of the C product to the precursor product in step (3) is (1-2.4):
1.
10. A process for preparing a PVDF profile according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, prepare the filler for standby use; S2, mixing the polyvinylidene fluoride and the filler, and then extruding and granulating at 250-300° C. to obtain the obtained product.
Citation Information
Patent Citations
Material special for polyvinylidene fluoride film
CN102010554A
Flame-retardant polyvinylidene fluoride film and preparation method thereof
CN102796334A
Fabric waterproof agent based on modified fluorosilicone resin and preparation method thereof
CN116623435A
Resin composition and insulating wire, wire and cable, tubing and heat-shrinkable tubing using the same
JP2006104395A
Thermoplastic Halogenated Polymer Composition
US20080227904A1